EFFECTS OF ANAESTHETICS ON THE BEHAVIOUR OF MULLET FINGERLINGS AND THE SCOPE OF USING THESE IN DIFFERENT FISHERY PROCEDURES n. Effects of Tertiary Amyl Alcohol, Ether, Quuialdine, Paraldehyde, Pentobarbital Sodium, Phenobarbital Sodium and MS-222 Sandox - Durve, V S (Indian Journal of Fisheries, 2011)
THE present paper is the continuation of the work by the author published earlier (Durve and Dharma Raja, 1966). Here, seven more anae&fetics in different concentrations have been tried in order t6 study their i^ects on the behaviour of fingerlings of the mullet Liza fade. This has enabled the author to select suitable anaesthetics—out of thirteen so far experimented with—for fishery work such as transport of live fish, tagging, fin-clipping, weighing, stripping and operating. Earlier work on the subject has been discussed by Durve and Dharma Raja (pp.cit.). At the end of the present paper, a general review of all the thirteen anaesthetics is given. Material and methods are the same as mentioned in the earlier paper (Durve and Dharma Raja op. cit.). All experiments were carried out in freshwater and at tempeatures ranging from 27 to 28° C